Evaluation of prescription pattern and quality of life in postmenopausal osteoporosis: a cross sectional study - Agrawal, Siddharth Pravin; Patel, Suhani V.; Malhotra, Supriya; Patel, Pankaj R. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Osteoporosis (OP) is a silently progressing metabolic bone disease that results in loss of mineralized bone and subsequent fractures with minor trauma. Fracture related pain and physical inability to perform activities of daily living can lead to psychological consequences that impair Quality of Life (QoF). However, much less is known about Indian scenario. Hence, our study becomes imperative. Aim of this study to the drug utilization pattern and to analyze Quality of life of postmenopausal women suffering from osteoporosis. Methods: An analytical cross-sectional study was done on 91 post-menopausal osteoporotic women. Drug utilization pattern was evaluated. Pre-validated QUALEFFO-31 questionnaire was administered to each patient to record patient’s perceived QoL. Scores were calculated according to the algorithm. Higher scores indicated poor QoL. The collected data was analyzed with SPSS software (version 23)and p value ≤0.05 was considered as statistically significant. Results: The mean age group of presenting patients was 56.2±6.6 years. All the patients received Calcium and vitamin D supplements and non-steroidal anti-inflammatory drugs for pain relief. But only 33% of the patients received any one of the bisphosphonates (BP). For analysis, patients were grouped into Group-1(n=60) who did not and Group-2 (n=31) who did receive a BP. QOL analysis showed that pain domain was affected the most. Also, patients in Group 2 reported worse score in all the domains in comparison to Group 1 (P<0.05). It is likely that BP might need more time to show considerable effect or because it was added only to those patients who already had more complaints and could afford the high cost. Conclusion: BP in spite of being the drug of choice for OP is used less commonly in India. OP causes pain and physical debilitation with detrimental effect on mental health. Longer duration prospective studies are needed to study the association of QoL and use of BP in OP patients.